Formation of Students' Social Ethics Through Social Science Learning at Sekolah Menengah Atas Negeri 4 Cirebon - Aziz, Amal Rizqi; Wasino, Wasino; Muh. Sholeh (Universitas Negeri Semarang, 2025)
The rapid advancement of information technology in the globalization era has significantly influenced teenagers' social interactions, particularly students at SMA Negeri 4 Cirebon. The widespread use of social media and digital platforms presents challenges in fostering social ethics among students. This study aims to develop an effective model for social ethics formation through Social Sciences (IPS) learning and to analyze the role of learning methods such as class discussions and experiential projects in integrating social ethical values ​​into students' daily lives. Employing a descriptive qualitative approach, data were collected through observations and in-depth interviews with teachers, students, and school administrators. Findings reveal that a collaborative approach between teachers and students, supported by the Pancasila Student Profile Strengthening Program (P5/P5 Student Profile Strengthening Program), effectively promotes social ethical values. Among the methods, project-based learning and class discussions are most effective in instilling tolerance, empathy, and social responsibility. This research contributes novelty by integrating social ethics within formal education, offering practical insights for character education strategies applicable to educators and policymakers.